2020
DOI: 10.1177/1937586720969933
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Design Strategies to Address Crowding and Boarding in an Emergency Department: A Discrete-Event Simulation Study

Abstract: Objective: To address prolonged lengths of stay (LOS) in a Level 1 trauma center, we examined the impact of implementing two data-driven strategies with a focus on the physical environment. Background: Crowding in emergency departments (EDs) is a widely reported problem leading to increased service times and patients leaving without being seen. Methods: Using ED historical data and expert estimates, we created a discrete-event simulation model. We analyzed the likely impact of initiating care and boarding pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Cubicles with curtains between patients, hallway bathrooms shared by multiple patients, small waiting rooms with the thought we would eliminate waiting with improved patient flow, lack of backup space for a surge in admissions, and multistation triage areas simply do not work with pandemics or even major trauma events. Airborne infections do not honor cubicle curtains as an effective barrier; epidemics with bodily fluid transmission (Ebola) require individual toilet areas; and multiple admissions simultaneously and crowding in the ED because of lack of intensive or acute care beds require contingency care settings adjacent to the ED (Valipoor et al, 2021). The design of “soft” spaces that can be rapidly deployed to increase surge capacity and maximizing adaptability of all spaces must be designed into new hospitals.…”
Section: Priority Design Topics For Healthcare and Design Practitionersmentioning
confidence: 99%
“…Cubicles with curtains between patients, hallway bathrooms shared by multiple patients, small waiting rooms with the thought we would eliminate waiting with improved patient flow, lack of backup space for a surge in admissions, and multistation triage areas simply do not work with pandemics or even major trauma events. Airborne infections do not honor cubicle curtains as an effective barrier; epidemics with bodily fluid transmission (Ebola) require individual toilet areas; and multiple admissions simultaneously and crowding in the ED because of lack of intensive or acute care beds require contingency care settings adjacent to the ED (Valipoor et al, 2021). The design of “soft” spaces that can be rapidly deployed to increase surge capacity and maximizing adaptability of all spaces must be designed into new hospitals.…”
Section: Priority Design Topics For Healthcare and Design Practitionersmentioning
confidence: 99%
“…The findings from this study displayed that the application of DES provides a cost-effective instrument to assess and inform future design decisions using current process data. Similar to previous studies (Cai & Jia, 2019;Han et al, 2010;Oh et al, 2016;Shim & Kumar, 2010b;Swan et al, 2019;Valipoor et al, 2021b), DES was notably worthwhile in evaluating the impact of multiple processes, design solutions, and proposing optimal scenarios for the ED.…”
Section: Discussionmentioning
confidence: 52%
“…These techniques include directing lowacuity patients to a co-located outpatient facility, public education, or increasing the working hours of primary care centers (Dolton & Pathania, 2016;Morley et al, 2018;Sharma & Inder, 2011). Other investigations have focused on expediting the patient flow within the ED system (Amarasingham et al, 2010;Bal et al, 2017;Copeland & Gray, 2015;Han et al, 2010;Valipoor et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Integration of isolated waiting room areas for potentially infectious patients who were otherwise stable allowed for a two-tiered approach to patient throughput. In addition, some studies that were published after the initiation of this study suggested other configurations (Franklin et al, 2020; Payne et al, 2020) or found other advantages of the retrieved strategies in the present study (Ahmadpour et al, 2021; Anderson et al, 2020; Martin et al, 2021; Valipoor et al, 2021) that provide insight for the future studies.…”
Section: Discussionmentioning
confidence: 59%